Enterococcus durans SL70, a Novel Exopolysaccharide Producer from Traditional Sourdough Fermentation of Einkorn (Triticum monococcum L. ssp. monococcum) - Berna Genc; Seyda Merve Karatas; Merve Tuğçe Tunç (Food Technology and Biotechnology)
Research background. Given the potential of microbial exopolysaccharides from lactic acid bacteria in various industrial processes, alternative sources for the isolation of lactic acid bacteria are highly topical. In this study, we used a traditional sourdough from einkorn (Triticum monococcum L. ssp. monococcum) as a source of lactic acid bacteria for the isolation, identification and determination of exopolysaccharide producers. Experimental approach. The sourdough was prepared from einkorn according to the traditional method. Lactic acid bacteria were isolated and purified using the single colony technique on MRS and M17 media. The isolates were characterised using matrix-assisted laser desorption ionization-time of flight mass (MALDI-TOF) spectrometry. All isolates were analysed for extracellular polysaccharide production and one isolate was selected for purification and characterisation of its polysaccharide. Results and conclusions. The isolates were identified as Lactobacillus plantarum, L. paraplantarum, L. brevis, Pediococcus pentosaceus, Enterococcus faecium and E. durans. The production of exopolysaccharides by all lactic acid bacteria was evaluated and it was found that all strains (except one) were capable of producing exopolysaccharides. One polysaccharide (EPS-SL70) was purified from the isolates of E. durans SL70. This anionic heteropolysaccharide had, in addition to the carbohydrate backbone, a protein structure that did not contain nucleic acid. The carbohydrate backbone consisted of mannose, glucose, rhamnose, arabinose, xylose and galactose. Novelty and scientific contribution. The microbial flora of traditional einkorn sourdough has been identified in this study and represents the first report on the exopolysaccharide production by lactic acid bacteria in traditional einkorn sourdough. Additionally, Enterococcus durans from einkorn sourdough was identified as a new exopolysaccharide producer.